France in the Global Economy : A Structural Approximate Dynamic Factor Model Analysis - Nadal De Simone, Francisco (IMF Working Papers; Working Paper ;, 2007)
This study identifies the main shocks that cause fluctuations in French output and their channels of transmission. It uses a large-dimensional structural approximate dynamic factor model. There are three main findings. First, common shocks, especially demand shocks, which seem to originate from the U.S., play an important role in explaining French economic activity. While international trade, relative prices, and FDI flows are the main channels of transmission, the stock market, consumer confidence, and interest rates also matter. Second, France's integration with the rest of the world has increased over time. Third, there is some tentative evidence of regional components in explaining French output fluctuations; countryspecific components also contribute. The predominance of exogenous factors affecting French output, the asymmetry in the transmission of shocks, and France's participation in a currency area, argue for making French goods, services, and labor markets as flexible as possible.